Clinical and Radiological Response Following Single-Session Gamma Knife Radiosurgery in Glomus Jugulare Tumors - Chaturvedi, Aprajita; Sadashiva, Nishanth; Thimmarayappa, Arun; Nagpal, Divisha; Baligar, Sushrut; Konar, Subhas; Beniwal, Manish; Prabhuraj, Andiperumal R.; Vazhayil, Vikas; Arimappamagan, Arivazhagan (Journal of Neurological Surgery Part B: Skull Base, 2025)
Glomus tumors are rare, slow-growing, hypervascular skull base tumors and frequently involve critical neurovascular structures. Surgical resection is technically challenging and is associated with high morbidity rates due to lower cranial nerve injury and CSF leak. Gamma knife radiosurgery (GKRS) has revolutionised the management of these lesions with high clinical and tumor control rates and a low side effect profile. In this study, we have attempted to study the tumor and clinical control rate along with the prediction factors.This is a retrospective data review of all patients with glomus jugulare tumors from 2010 to 2023 who underwent GKRS in our center. Clinical, neuroimaging, and radiosurgical treatment were re-reviewed, and all patients' prognostic factors for clinical and tumor control were analyzed.The study included 95 patients. The median age was 45 years, with three-fourths of our patients being female, 69 (72.6%). Hearing loss was the most common symptom. The median marginal dose at the 50% isodose line was 16 Gy. The mean tumor volume was 8.7 cc, and the mean treatment volume was 8.3 cc. The tumor control rate in our study period was 96.9%. Younger age and Glasscock–Jackson type 1 were found to be worse and a good prognostic factor, respectively. The clinical control rate in our study was 93.9%, with no related significant prognostic variable in our study.Gamma knife is a safe and effective treatment option for these formidable tumors with a very low complication rate.
Keywords: glomus jugulare tumor; radiosurgery; gamma knife radiosurgery; lower cranial nerve